"Perfectly Positioned": The Blurring of Urban, Suburban, and Rural Boundaries in a Southern Community. Issue 1 (July 2017) - Garner, Betsie
In this article, I draw on ethnographic fieldwork and formal interviews from a community study in Rockdale County, Georgia, to illustrate the social construction of place-based identity within the rural-urban interface. Given decades of growth and expansion in metro Atlanta, Rockdale has become an object lesson of the boundary shifting and crossing typical of places located along the rural-urban fringe. A sustained pattern of demographic and ecological change in Rockdale has resulted in a lack of consensus about how to imagine the community's location on the rural-urban continuum. I show how symbolic and social boundaries between urbanity and rurality are blurred within the community as residents draw on local resources to construct alternatively urban, suburban, and rural identities. Additionally, I illustrate how local boosters take advantage of this blurriness to portray Rockdale County as a "perfectly positioned" community and how community members disregard the official rural-urban boundaries of governments or scholars and instead invest their own imagined boundaries with significant meaning.